2016
DOI: 10.4196/kjpp.2016.20.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid protects against acetaminophen-induced hepatotoxicity by potentiating Nrf2-mediated antioxidant capacity in mice

Abstract: Acetaminophen (APAP) overdose is one of the most common causes of acute liver failure. The study aimed to investigate the protective effect of carnosic acid (CA) on APAP-induced acute hepatotoxicity and its underlying mechanism in mice. To induce hepatotoxicity, APAP solution (400 mg/kg) was administered into mice by intraperitoneal injection. Histological analysis revealed that CA treatment significantly ameliorated APAP-induced hepatic necrosis. The levels of both alanine aminotransferase (ALT) and aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
5
19
1
Order By: Relevance
“…It is conceivable in our study that carnosic acid rescued the liver against acrylamide in a way that the body did not need to activate Nrf2 activation, which is related to bodily antioxidant‐oxidant balance. In contrast to our study, Guo et al [ 35 ] reported that carnosic acid facilitated Nrf2 translocation and stimulated genes associated with Nrf2 in a study in which the protective role of carnosic acid in acetaminophen‐induced hepatotoxicity in mice was demonstrated. This discrepancy might stem from different experimental duration and substance dose regimen as well as the interplay between the toxic and the protective substances.…”
Section: Discussioncontrasting
confidence: 99%
“…It is conceivable in our study that carnosic acid rescued the liver against acrylamide in a way that the body did not need to activate Nrf2 activation, which is related to bodily antioxidant‐oxidant balance. In contrast to our study, Guo et al [ 35 ] reported that carnosic acid facilitated Nrf2 translocation and stimulated genes associated with Nrf2 in a study in which the protective role of carnosic acid in acetaminophen‐induced hepatotoxicity in mice was demonstrated. This discrepancy might stem from different experimental duration and substance dose regimen as well as the interplay between the toxic and the protective substances.…”
Section: Discussioncontrasting
confidence: 99%
“…The levels of serum AST, ALT and LDH are the most sensitive biomarkers that can directly indicate the extent of hepatic damage. (29) APAP caused a significant increase in the levels of AST, ALT and LDH (Fig. 2).…”
Section: Discussionmentioning
confidence: 89%
“…NF-κB also modulates the expression of a variety of genes, including the genes encoding iNOS and COX-2, resulting in an increased production of TNF-α and NO in tissues [ 49 ]. APAP was shown to activate the NF-κB pathway by promoting NF-κB translocation [ 49 ] and IκBα degradation [ 50 ]. In this study, APAP-induced NF-κB translocation was blocked by either TA or NAC ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%